In Situ Frost-Heaving Characteristics of Shallow Layer of Soil Slopes in Intermittently Frozen Region Based on PFC3D. (13th March 2021) - Ke, Yunbin; Que, Yun; Fu, Yuanshuai; Jiang, Zhenliang; Easa, Said; Chen, Yanyu
Abstract : The in situ frost-heaving (FH) process and characteristics of the shallow layer of a residual soil slope in the intermittently frozen zone were simulated by a modified three-dimensional particle flow code (PFC 3D ) model, of which the mesoscopic parameters of soil and ice particles were calibrated through the indoor experiments. In this model, the in situ FH process was gradually achieved by expanding the volume of ice particles (divided into 24 times of expansion), and the process was terminated when the monitored porosity was stable. These countermeasures avoided the stress accumulation and effectively realized the simulation of the in situ FH process. The results found that the displacement occurred firstly and got the largest final value at the surface angle (SA) under the in situ FH effect, followed by that at the foot, and it gradually extended to the interior based on these two regions. The vertical tension was present at the SA, and the major force type in the lateral interlayer was pressure. In addition, the FH effect seemed to be strongly related to the frozen depth, and a sliding surface was found in a steeper slope. Finally, the smaller stone appeared to be favorable to the slope stability, but it was reduced by the larger stone to some extent.